2020
DOI: 10.3802/jgo.2020.31.e24
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1/2mutation status in patients with metachronous breast and ovarian malignancies: clues towards the implementation of genetic counseling

Abstract: Objective: The characteristics of patients with metachronous breast and ovarian malignancies and the pathogenic role of BRCA1/2 mutations remain poorly understood. We investigated these issues through a review of hospital records and nationwide Taiwanese registry data, followed by BRCA1/2 mutation analysis in hospital-based cases. Methods: We retrospectively retrieved consecutive clinical records of Taiwanese patients who presented with these malignancies to our hospital between 2001 and 2017. We also collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Another study showed that c.4065_4068del is one of the three most common BRCA1 variants in Chinese ovarian cancer patients [ 47 ]. In the BRCA2 gene, c.5164_5165delAG has been detected in the Chinese Han population [ 64 ], Macau population [ 65 ], and Taiwanese populations [ 66 ]. BRCA2 c.2339C > G has been detected in Taiwanese [ 67 ], and Japanese [ 68 ] individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that c.4065_4068del is one of the three most common BRCA1 variants in Chinese ovarian cancer patients [ 47 ]. In the BRCA2 gene, c.5164_5165delAG has been detected in the Chinese Han population [ 64 ], Macau population [ 65 ], and Taiwanese populations [ 66 ]. BRCA2 c.2339C > G has been detected in Taiwanese [ 67 ], and Japanese [ 68 ] individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were selected by the following inclusion criteria: 1) cancer patients should be pathologically confirmed, 2) germline variants in BRCA1/2 should be genotyped, and 3) studies on nonhuman or cell line were excluded. Thoroughly searching PubMed and Google Scholar using the keywords such as “ BRCA1 ” “ BRCA2 ” “Taiwan” “Taiwanese” and “cancer predisposition” we identified 15 publications reporting the BRCA data from Taiwanese cancer patients between 1997 and 2020 ( Liu et al, 1997 ; Li et al, 1999 ; Wang et al, 2000 ; Chen et al, 2003 ; Lin et al, 2003 ; Chen et al, 2005 ; Chang et al, 2006 ; Kuo et al, 2012 ; Chao et al, 2016 ; Lin et al, 2016 ; Sung et al, 2017 ; Wang et al, 2018 ; Lin et al, 2019 ; Chao et al, 2020 ; Lin et al, 2020 ). Searching Taiwan Biobank ( https://taiwanview.twbiobank.org.tw/index ; accessed December 15, 2020) using the keywords “ BRCA1 ” and “ BRCA2 ” we obtained the BRCA variation data derived from Taiwanese general population.…”
Section: Methodsmentioning
confidence: 99%
“…A high proportion of mutations were in BRCA1/2 genes, they were identified in 10% of OV cancer patients and 35.5% of BROV cancer patients. A high BRCA1/2 mutation rate of 38.9% has also been demonstrated in Taiwan in a cohort of 18 synchronous/metachronous BROV cancer studies (Chao et al, 2020 ). BRCA1/2 mutations (14.6%–22.8%) were more likely found in high‐grade serous carcinoma of ovarian than other types of ovarian cancer (Alsop et al, 2012 ; Candido‐dos‐Reis et al, 2015 ; Harter et al, 2016 ).…”
Section: Discussionmentioning
confidence: 79%
“…Mutations in BRCA1/2 genes were detected in approximately 12%–25% of patients with high‐grade serous ovarian carcinoma (HGSC) (Chao et al, 2016 ; Sakamoto et al, 2016 ; Walsh et al, 2011 ) while the prevalence of BRCA1/2 mutation was (3.7%–4.7%) in women with breast cancer, aged between 40 and 59 years (Buys et al, 2017 ). The BRCA1/2 mutation rate in 18 Chinese cohorts with metachronous BROV malignancies was as high as 38.9% (Chao et al, 2020 ). There were well‐established counseling strategies and management guidelines for early intervention or prevention through increased surveillance, such as clinical breast examination every 6–12 months and addition of annual breast MRI, mammography at age 25, and consideration of risk‐reducing interventions including chemoprevention and prophylactic mastectomy or salpingo‐oophorectomy (Petrucelli et al, 1998 ; Smith, 2012 ).…”
Section: Introductionmentioning
confidence: 99%